Development of Minimum Competency Assessment (AKM) Model Test for Learning Biology Excretion System Materials for Measuring Science Literacy in SMA Negeri 1 Bandar - Ajeng Suwastikasari; saiful ridlo (Journal of Biology Education, 2023)
The results of the 2018 PISA study show that the ability of students in Indonesia in scientific literacy shows an average score of 389, so scientific literacy is still low. The Ministry of Education and Culture released the Independent Learning Program to replace the National Examination (UN) assessment system with a Minimum Competency Assessment (AKM) and character surveys. Therefore, it is necessary to develop AKM questions on the excretory system material to measure scientific literacy in students. The purpose of this study is to describe the characteristics of the AKM model questions, analyze differences in student learning outcomes and student responses related to the AKM model questions at SMA Negeri 1 Bandar, Batang Regency. This research refers to the development of questions according to Djemari Mardapi which consists of 7 stages that have been modified, The subjects of this study were students of class XI MIPA 4 (experimental class) and class XI MIPA 5 (control class). Analysis of the items on the test results of the AKM model test using Microsoft Excel software and SPSS v.19 software. That is to calculate validity, difficulty index, discriminating power and reliability estimation. Data on the results of differences in student learning averages were measured using a test instrument for the AKM model and student response data was measured using a questionnaire instrument. The results of the study obtained from 25 questions that were tested on students there were 23 valid questions and 2 invalid questions, the results of the difficulty level on the items obtained 12 very easy questions and 13 easy questions, the results of the differentiating power were in the good category and the results of the reliability estimation of items The questions are included in the very high category, and the results of the difference in the average learning outcomes in the experimental class and control class are 73.61> 61.44. The increase in the average learning outcomes of experimental and control class students in their scientific literacy skills was significantly different with an N-gain value of 58.28 > 25.08. The experimental class gave a very good response and the control class gave a good response to the development of the AKM model questions. Thus, it can be concluded that the development of the AKM model test questions can measure students' scientific literacy skills.